2007
DOI: 10.1080/07399330601001402
|View full text |Cite
|
Sign up to set email alerts
|

The Leisure Experiences of Older U.S. Women Living With HIV/AIDS

Abstract: Although leisure is held to provide positive health benefits, structural and social obstacles deny equal participation to the disenfranchised. Employing quantitative and unique qualitative (e.g., Photovoice) methods, we examined the leisure behaviors of older women who were living in the United States and diagnosed with HIV/AIDS. Findings pointed to differences in time for, access to, and meaning of leisure in pre- vs. post-infection leisure for these women. As the disease progressed, however, each woman exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 32 publications
2
29
0
3
Order By: Relevance
“…They found that the episodic nature of the illness led to uncertainty about current care and future needs as well as an inability to plan. Gosselink and Myllykangas (2007), in their study of women with HIV, found inequalities of health and leisure resources. Yet, each woman showed resilience.…”
Section: Living With Hivmentioning
confidence: 95%
“…They found that the episodic nature of the illness led to uncertainty about current care and future needs as well as an inability to plan. Gosselink and Myllykangas (2007), in their study of women with HIV, found inequalities of health and leisure resources. Yet, each woman showed resilience.…”
Section: Living With Hivmentioning
confidence: 95%
“…Photovoice has been used in a variety of populations and cultures including people who are homeless (Wang, Cash, & Powers, 2000), children and youth (Fitzgerald, Bunde-Birouste, & Webster, 2009;Gant et al, 2009;Goodhart et al, 2006;Wang, 2006;Wilson, Minkler, Downloaded by [Chulalongkorn University] at 08:50 03 January 2015 Dasho, Wallerstein, & Martin, 2008), older adults (Baker & Wang, 2006;Lockett, Willis, & Edwards, 2005), and those living with specific disease processes (Aubeeluck & Buchanan, 2006;Gosselink & Myllykangas, 2007;Hergenrather, Rhodes, & Clark, 2006). However, it is especially appropriate and effective when applied to women's health (Booth & Booth, 2003;McIntyre, 2003;Moffit & Vollman, 2004;Valera, Gallin, Schuk, & Davis, 2010;Vaughn et al, 2009;Wang, 1999;Wang & Pies, 2004).…”
Section: Photovoicementioning
confidence: 99%
“…To date, research that has focused on resilience among people living with HIV in the US has focused almost exclusively on adults, [38][39][40][41][42][43] with a particular emphasis on older adults. [44][45][46] The population and context-specific nature of resilience calls for attention to the potential role of race and ethnicity in the development and promotion of resilience among YGBM living with HIV, especially if such information will be used for the development of culturally appropriate secondary prevention interventions. 26 In addition to the oppressive forces these youth may experience related to their sexual orientation and HIV status, African American and Latino YGBM living with HIV may experience additional layers of oppression related to their social and cultural identities.…”
Section: Introductionmentioning
confidence: 99%